Pediatric diarrhea patients living in urban areas have a higher incidence of Clostridioides difficile infection - Ayodele T. Adesoji; Osaro Mgbere; Charles Darkoh (Public Library of Science (PLoS), 2023)
Clostridioides difficile infection (CDI) is a major cause of antibiotic-associated diarrhea and an unappreciated contributor to child mortality in low- and middle-income countries where the diagnosis may be difficult. There is little information about the prevalence of CDI among infants, children, and adolescents in Africa. Using a cross-sectional design, seventy-six samples were collected from pediatric patients presenting with diarrhea, including infants (≤ 2 years old), children (2-12 years), and adolescents (13 ≤17 years) from three hospitals between January and December 2019. Demographic data, medical history, and prior antibiotic use were recorded. Toxigenic culture and PCR were used to detect and validate the presence of C. difficile in the samples. Data obtained were analyzed using descriptive and inferential statistics. A total of 29 (38.7%), 39 (52.0%) and 7 (9.3%) samples were from infants, children, and adolescents, respectively. The average age of the patients was 4.4 years. Of these samples, 31 (41%) were positive for C. difficile by culture and were verified by PCR amplification of C. difficile-specific genes (tcdA and tcdB). The most positive cases were children (53.3%) and infants (40.0%) with the majority of them residing in urban areas. Forty-nine (66.2%) of the patients had no known antibiotics exposure, whereas 29.0% and 29.7% reported the use of over-the-counter antibiotics at 14 and 90 days, prior to the hospital visit, respectively. CDI is relatively common among children with diarrhea in Northern Nigeria. Therefore, for effective management and treatment, more attention should be given to testing for C. difficile as one of the causative agents of diarrhea.